Oriental Teratomyzidae (Diptera: Schizophora) - Papp, László (Zootaxa, 2011)
The Oriental Teratomyzidae (Diptera) are reviewed. Teratomyza formosana sp. nov. is described and compared to T. chinica Yang. Poecilovitila gen. nov. (type species: P. elegans sp. nov.), a genus related to Vitila McAlpine & Keyzer is described, and includes eleven new species P. barbata sp. nov., P. brevicornis sp. nov., P. bulbiscapus sp. nov., P. defecta sp. nov., P. elegans sp. nov., P. erugata sp. nov., P. hindustanica sp. nov., P. japonica sp. nov., P. taiwanica sp. nov., P. thaii sp. nov., P. variegata sp. nov.).